Bacterial community structure, compartmentalization and activity in a microbial fuel cell - Kim, G. T.; Webster, G.; Wimpenny, J. W. T.; Kim, B. H.; Kim, H. J.; Weightman, A. J. (BLACKWELL PUBLISHING, 2006)
Aims: To characterize bacterial populations and their activities within a microbial fuel cell (MFC), using cultivation-independent and cultivation approaches. Methods and Results: Electron microscopic observations showed that the fuel cell electrode had a microbial biofilm attached to its surface with loosely associated microbial clumps. Bacterial 16S rRNA gene libraries were constructed and analysed from each of four compartments within the fuel cell: the planktonic community; the membrane biofilm; bacterial clumps (BC) and the anode biofilm. Results showed that the bacterial community structure varied significantly between these compartments. It was observed that Gammaproteobacteria phylotypes were present at higher numbers within libraries from the BC and electrode biofilm compared with other parts of the fuel cell. Community structure of the MFC determined by analyses of bacterial 16S rRNA gene libraries and anaerobic cultivation showed excellent agreement with community profiles from denaturing gradient gel electrophoresis (DGGE) analysis. Conclusions: Members of the family Enterobacteriaceae, such as Klebsiella sp. and Enterobacter sp. and other Gammaproteobacteria with Fe(III)-reducing and electrochemical activity had a significant potential for energy generation in this system. Significance and Impact of the Study: This study has shown that electrochemically active bacteria can be enriched using an electrochemical fuel cell.
Keywords: METAL-REDUCING BACTERIUM; FE(III)-REDUCING BACTERIUM; ELECTRON-TRANSFER; ACTIVATED-SLUDGE; SHEWANELLA-PUTREFACIENS; ELECTRICITY PRODUCTION; DISSIMILATORY FE(III); AEROMONAS-HYDROPHILA; GRAPHITE-ELECTRODES; NEUTRAL RED